Association of Simvastatin and Hyperlipidemia With Periodontal Status and Bone Metabolism Markers. Issue 10 (1st October 2014) - Magán‐Fernández, Antonio; Papay‐Ramírez, Lara; Tomás, Juan; Marfil‐Álvarez, Rafael; Rizzo, Manfredi; Bravo, Manuel; Mesa, Francisco
Abstract : Background: The objective of this study is to determine whether simvastatin consumption and hyperlipidemia are associated with a worse periodontal condition and specific bone activity biomarkers. Methods: This cross‐sectional and analytic study includes 73 patients divided into three groups: 1) simvastatin‐treated patients with hyperlipidemia (n = 29); 2) patients with hyperlipidemia treated by diet alone (n = 28); and 3) normolipidemic patients (controls, n = 16). The periodontal clinical variables of all participants were gathered, a blood sample was drawn from each to determine the lipid profile (total cholesterol, triglycerides, low‐density lipoprotein, and high‐density lipoprotein), serum levels of acute‐phase reactants (C‐reactive protein), erythrocyte sedimentation rate, and bone metabolism markers (osteoprotegerin [OPG], osteocalcin, procollagen type I N‐terminal propeptide, and C‐terminal telopeptide of type I collagen). Results: The mean ESR was higher in the diet‐treated patients with hyperlipidemia than in the normolipidemic controls ( P = 0.04). Serum OPG concentrations were significantly higher in the simvastatin‐treated patients with hyperlipidemia than in the diet‐treated patients with hyperlipidemia ( P = 0.05). Multivariable linear regression analysis adjusted for age, sex, tobacco, and alcohol revealed that, compared with the normolipidemic patients, the simvastatin‐treated patients with hyperlipidemia showed a mean reduction of 0.8 mm (95% confidence interval = −1.5 to 0.0, P = 0.05) in clinical attachment loss. Conclusions: Within the limits of this study, the findings suggest that the intake of simvastatin is associated with increasing serum OPG concentrations, and this could have a protective effect against bone breakdown and periodontal attachment loss. The baseline systemic inflammatory state of patients with hyperlipidemia is indicated by their increased erythrocyte sedimentation rate.